GE_GERICHTE P/719/2001 vom 29. November 2011 - GE Cour de justice (2011)
; CONSULTATION DU DOSSIER ; CONFISCATION(DROIT PÉNAL) ; BLANCHIMENT D'ARGENT ; COMPÉTENCE RATIONE LOCI ; CRIME ; PRESCRIPTION | CP.305bis; CP.97; CP.98; CP.8; CP.10; CPP.107